Дворянское гнездо: 1858-1860 / [примечания М. П. Алексеева] - Тургенев Иван Cергеевич (1981)
Экземпляры: ЧЗ (20160309) / Инвентарный номер: 2051 / Цена: 3.40 / Сис.шифр: Р1 / Авт.знак: Т 87 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1